Level of Evidence as a Future Gold Standard for the Content Quality of Health Resources on the Internet - Darmoni, S. J.; Amsallem, E.; Haugh, M.; Lukacs, B.; Leroux, V.; Thirion, B.; Weber, J.; Boissel, J. P. (Methods of Information in Medicine, 2003)
Objective: An assessment of the quality of health information on the Internet is an absolute necessity. In this study ‘sensitive’ information was defined as information found in documents published on the Internet, which could be used in a medical decision. For sensitive information, the main criterion chosen for the quality of the information was an indication of the level of evidence. A survey was conducted using the CISMeF health catalogue to assess how often a score of the level of evidence is mentioned in the information accessible on the Internet in French-language health resources.Methods: Since 1999, members of the CISMeF team have systematically been searching for all documents containing ‘sensitive’ information and verifying whether the level of evidence was explicitly indicated as a score at least once in the document.Results: As of June 2001, 10,190 resources were included in CISMeF; including 2964 textual ‘sensitive’ resources (29.1%). Out of all these resources, only 4.7% (95% confidence interval: 4.0 - 5.5%) indicated the level of evidence. A statistically significant difference in the prevalence of indicating the level of evidence according to resource types (e.g., 18.1% for guidelines compared to 0.0% for teaching material), year of publication (almost three times greater in 1997-2001 compared with 1990-1996) and publishers was observed.Conclusion: As the number of people accessing the growing amount of information on the Internet is increasing daily, publishers have an ethical obligation to inform their readers about the validity of ‘sensitive’ information their sites contain. However, the vast majority of the French language Internet resources that were surveyed do not mention a score of the level of evidence for their sensitive information.
Keywords: Internet; quality control; evidence-based medicine; level of evidence